Why Did China's Assertive Strategy on the Himalayan Border? - Surwandono, Surwandono; Silitonga, Derina Faslig (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2022)
The development of differing perceptions of the Line of Actual Control (LAC) has been one of the constant factors leading to the protracted dispute in the Himalayan border. Since the outbreak of war in 1962, recriminations and clashes between military forces have continued along the 3,488 km disputed area. Since 1980 both parties have continued to make efforts to resolve disputes with a fair and acceptable solution. Unfortunately, the initiations of these peace efforts have always been deadlocked. At first, in responding to India, China preferred to be passive. However, recently China has begun to respond with an assertive behavior. The deployment of army troops, military equipment, covert attacks, and massive infrastructure development was carried out by China in strategic Himalayan border. This study explores the changing of China’s assertive strategy in the Himalayas by employing offensive realism and using qualitative approach. This study has found that the changing behavior of China’s is related protecting its national interests and territorial sovereignty as well as a form of affirming the stability of China's dominance in the region. This study's results will provide an overview that there has been a shift in China's strategy for managing its border conflict with India.